Research and Data Priorities for Improving Economic and Social Mobility: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
Since around 1980, fewer Americans than before are doing better than their parents had 2013 that is, more are experiencing downward social and economic mobility in terms of occupational status and income. This trend in downward mobility is occurring amidst high and rising levels of inequality in income, wealth, health, and life expectancy. To better understand the factors that influence social and economic mobility, the Committee on Population and the Committee on National Statistics hosted a workshop on February 14-15, 2022. The proceedings from this workshop identify key priorities for future research and data collection to improve social and economic mobility.

Collecting Compensation Data from Employers - National Research Council (The National Academies Press, 2012)
U.S. agencies with responsibilities for enforcing equal employment opportunity laws have long relied on detailed information that is obtained from employers on employment in job groups by gender and race\/ethnicity for identifying the possibility of discriminatory practices. The U.S. Equal Employment Opportunity Commission (EEOC), the Office of Federal Contract Compliance programs of the U.S. Department of Labor, and the Civil Rights Division of the U.S. Department of Justice have developed processes that use these employment data as well as other sources of information to target employers for further investigation and to perform statistical analysis that is used in enforcing the anti-discrimination laws. The limited data from employers do not include (with a few exceptions) the ongoing measurement of possible discrimination in compensation. The proposed Paycheck Fairness Act of 2009 would have required EEOC to issue regulations mandating that employers provide the EEOC with information on pay by the race, gender, and national origin of employees. The legislation was not enacted. If the legislation had become law, the EEOC would have been required to confront issues regarding currently available and potential data sources, methodological requirements, and appropriate statistical techniques for the measurement and collection of employer pay data. The panel concludes that the collection of earnings data would be a significant undertaking for the EEOC and that there might be an increased reporting burden on some employers. Currently, there is no clearly articulated vision of how the data on wages could be used in the conduct of the enforcement responsibilities of the relevant agencies. Collecting Compensation Data from Employers gives recommendations for targeting employers for investigation regarding their compliance with antidiscrimination laws.

Research and Development Data Needs: Proceedings of a Workshop - National Research Council (The National Academies Press, 2005)
This report contains the proceedings of a one-day workshop organized by the National Research Council2019s Board on Science, Technology, and Economic Policy (STEP), in conjunction with a study by a panel of the NRC Committee on National Statistics (CNSTAT). This combined activity was commissioned by the Science Resources Statistics Division (SRS) of the National Science Foundation (NSF) to recommend improvements in the Foundation2019s portfolio of surveys of research and development spending by the federal government, state governments, private industry, the nation2019s universities and colleges, and other nonprofit institutions.

Using Human Resource Data to Track Innovation: Summary of a Workshop - National Research Council (The National Academies Press, 2002)
Despite the fact that technology is embodied in human as well as physical capital and that interactions among technically trained people are critical to innovation and technology diffusion, data on scientists, engineers and other professionals have not been adequately exploited to illuminate the productivity of and changing patterns in innovation. STEP convened a workshop to examine how data on qualifications and career paths, mobility, cross sector relationships, and the structure of work in firms could shed light on issues of research productivity, interactions among private and public sector institutions, and other aspects of innovation.

Understanding Business Dynamics: An Integrated Data System for America's Future - National Research Council (The National Academies Press, 2007)
The U.S. economy is highly dynamic: businesses open and close, workers switch jobs and start new enterprises, and innovative technologies redefine the workplace and enhance productivity. With globalization markets have also become more interconnected. Measuring business activity in this rapidly evolving environment increasingly requires tracking complex interactions among firms, establishments, employers, and employees. Understanding Business Dynamics presents strategies for improving the accuracy, timeliness, coverage, and integration of data that are used in constructing aggregate economic statistics, as well as in microlevel analyses of topics ranging from job creation and destruction and firm entry and exit to innovation and productivity. This book offers recommendations that could be enacted by federal statistical agencies to modernize the measurement of business dynamics, particularly the production of information on small and young firms that can have a disproportionately large impact in rapidly expanding economic sectors. It also outlines the need for effective coordination of existing survey and administrative data sources, which is essential to improving the depth and coverage of business data.

Improving the Design of the Scientists and Engineers Statistical Data System (SESTAT) - National Research Council (The National Academies Press, 2003)
The past decade has demonstrated the utility of SESTAT, but the SESTAT design shows some deficiencies with respect to response rates, coverage of populations of interest, and its ability to support some useful analyses. To tackle those deficiencies, NSF has proposed three possible design options for improving the database and asked the National Research Council's Committee on National Statistics (CNSTAT) to form the Committee to Review the 2000 Decade Design of the SESTAT.This is the report of that committee. It presents our understanding of the purposes and characteristics of the SESTAT, applies the criteria we believe are important for assessing design options for the database, provides our recommendation for the best approach to adopt in the 2000 decade, and offers our encouragement to NSF to pursue opportunities to improve the understanding of the numbers and characteristics of scientists and engineers in the United States.

Surveying the Nation's Scientists and Engineers: A Data System for the 1990s (The National Academies Press, 1989)

Analysis of Job Performance Measurement Data: Report of a Workshop - National Research Council (The National Academies Press, 1988)

Industrial Ecology: U.S.-Japan Perspectives (The National Academies Press, 1994)

Short-Term Strategies for Addressing the Impacts of the COVID-19 Pandemic on Women's Workforce Participation - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2021)
The COVID-19 pandemic and the associated recession have significantly affected women2019s workforce participation. These impacts have varied from job loss to additional caregiving responsibilities. Black and Hispanic women have been particularly affected, bringing into sharp relief historical gender and racial inequities in the labor market. In order to address the impacts of the COVID-19 pandemic and resulting recession on women's employment, state and local decision makers can use available federal funds to mitigate those impacts while also laying the foundation for longer-term solutions. This rapid expert consultation identifies strategies that state and local decision makers can use to assist in short-term recovery efforts for women whose employment status and work experiences have been affected by the COVID-19 pandemic. It includes strategies both for supporting caregiving responsibilities and career development. This rapid expert consultation was produced through the Societal Experts Action Network (SEAN), an activity of the National Academies of Sciences, Engineering, and Medicine that is sponsored by the National Science Foundation and the Alfred P. Sloan Foundation. SEAN links researchers in the social, behavioral, and economic sciences with decision makers to respond to policy questions arising from the COVID-19 pandemic. This project is affiliated with the National Academies' Standing Committee on Emerging Infectious Diseases and 21st Century Health Threats. The white papers that informed the development of this rapid expert consultation were commissioned by the National Bureau of Economic Research with the support of the Alfred P. Sloan Foundation.

Supply Chain Disruptions: Impacts on Vulnerable Communities: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2024)
The pervasive effects of supply chain disruptions, underscored by the COVID-19 pandemic, climate change, and critical shortages of essential commodities, reverberate through all communities. Evidence exists, however, that these impacts are not evenly distributed and are disproportionately intense and persistent among vulnerable populations. Recovery from supply chain disruptions also takes longer in vulnerable and marginalized communities, and the disproportionate impacts of these disruptions have economic justice and equity implications. On September 12, 2023, the Science and Technology for Resilience Program at the National Academies of Sciences, Engineering, and Medicine convened a virtual workshop to understand how vulnerable communities are at risk of being impacted by supply chain disruptions; challenges faced in mitigation, preparedness, response, and recovery; sustainability strategies for overcoming these challenges; and examples of adaptive, resilient, and sustainable efforts undertaken by communities to lessen impacts and develop actionable policies, programs, and strategies. This publication summarizes the presentations and discussion of the workshop.

Counting Injuries and Illnesses in the Workplace: Proposals for a Better System - National Research Council (The National Academies Press, 1987)

The Survey of Income and Program Participation: An Interim Assessment (The National Academies Press, 1989)

The International Technology Transfer Process (The National Academies Press, 1980)

Income and Poverty Statistics: Problems of Concept and Measurement: Report of a Workshop - National Research Council (The National Academies Press, 1988)

Foreign Construction Costs: Summary of a Symposium (The National Academies Press, 1991)

Balancing the National Interest: U.S. National Security Export Controls and Global Economic Competition, Working Papers (The National Academies Press, 1987)

Construction Contract Modifications: Comparing the Experiences of Federal Agencies With Other Owners (The National Academies Press, 1986)

Export Controls: Reconciling National Objectives, Selected Presentations From an Academy Industry Program Seminar Held in Washington, D.C., on February 14, 1984 (The National Academies Press, 1984)

Toward an Improved U.S. Merchant Marine: A Recommended Program of Studies (The National Academies Press, 1976)